Bullets that changed America: thirteen historic assassinations, duels, misfires and murders - Zablocki, Peter (McFarland & Company, Inc., Publishers, 2022)
An unfortunate encounter, May 28, 1754 -- "Back to your mark, sir!" May 30, 1806 -- Death of a prophet, October 5, 1813 -- They came in the night, May 28, 1856 -- "Halt, who goes there?" May 2, 1863 -- A "square" fight, May 3, 1886 -- Black coyote's rifle, December 29, 1890 -- Wilson's Wilson problem, February 22, 1913 -- An afternoon holdup, April 15, 1920 -- The unfortunate bonus, July 28, 1932 -- Machine gun challenge to Uncle Sam, June 17, 1933 -- A catalyst for change, February 18, 1965 -- Sins of our fathers, March 16, 1968.